PERBANDINGAN HASIL BELAJAR KIMIA SISWA ANTARA MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN CORE DI SMAN 2 KOTA BENGKULU TAHUN PELAJARAN 2018/2019 - Citra Utari; Salastri Rohiat; Nurhamidah Nurhamidah (ALOTROP, 2020)
This study aims to see whether or not there are differences in student chemistry learning outcomes between classes that apply STAD and CORE type cooperative learning models to buffer solution material in class XI MIPA Bengkulu City 2 High School 2018/2019. The study was conducted in March-April 2019. This type of research is Quasi research experiments. The population of this study was students of class XI MIPA with a population of 243 students. Sampling was carried out after the homogeneity and normality test, so the class XI MIPA A and XI MIPA B was selected as the research sample with random sampling technique with a sample of 60 students. The first experimental class uses the STAD learning model and the experimental class II uses the CORE learning model. Student learning outcomes data obtained from the value of the pretest and posttest. The two treatments given can improve learning outcomes with the average value of the pretest of experimental class I and experiment II namely 27.83 and 33.83 then the average value of the posttest of experimental class I and experiment II is 80 and 80.2 which means the posttest value has reached KKM which is 75. Hypothesis testing is done using a significant level (? = 0.05), the value obtained for t count> t table is 2,286> 1,672. These results can be concluded that there are significant differences in learning outcomes between the experimental class I and experiment II on the buffer solution material